LANDASAN AKSIOLOGIS PEMIKIRAN BUNG HATTA TENTANG DEMOKRASI - Zubaidi, Ahmad (Jurnal Filsafat "WISDOM", 2011)
Hatta has a specific concept of democracy in which there are some differences from liberal democracy. One of them is based on its axiological ground. Therefore, the purposes of this research are to analyze Hatta’s thought on democracy and its axiological ground. The primary data is taken from Hatta’s works,they are : Demokrasi Kita (1978), Pengertian Pancasila (1981), and Kumpulan Pidato , 3 volumes (1985).The results of this research are : Hatta’s concept of democracy for Indonesia is not similar at all with the Western concept of liberal democracy. Hatta developed the Indonesian democracy as a specific concept which its principles base on the original values within Indonesian society. His concept embraces political, economical and social aspects. From the axiological perspective, Hatta’s concept of democracy is based on the fundamental values, such as truth, justice, goodness, honesty, beauty, and holiness. Therefore, it can be said that the fundamental values in Hatta’s concept of democracy embrace ethic, aesthetic, and religious values.Keywords: democracy, axiological ground, fundamental values.